A chromosome-level genome assembly of the Korean crossbred pig Nanchukmacdon (Sus scrofa) - Daehong Kwon; Nayoung Park; Suyeon Wy; Daehwan Lee; Han-Ha Chai; In-Cheol Cho; Jongin Lee; Kisang Kwon; Heesun Kim; Youngbeen Moon; Juyeon Kim; Woncheoul Park; et al. (Scientific Data, 2023)
Abstract As plentiful high-quality genome assemblies have been accumulated, reference-guided genome assembly can be a good approach to reconstruct a high-quality assembly. Here, we present a chromosome-level genome assembly of the Korean crossbred pig called Nanchukmacdon (the NCMD assembly) using the reference-guided assembly approach with short and long reads. The NCMD assembly contains 20 chromosome-level scaffolds with a total size of 2.38 Gbp (N50: 138.77 Mbp). Its BUSCO score is 93.1%, which is comparable to the pig reference assembly, and a total of 20,588 protein-coding genes, 8,651 non-coding genes, and 996.14 Mbp of repetitive elements are annotated. The NCMD assembly was also used to close many gaps in the pig reference assembly. This NCMD assembly and annotation provide foundational resources for the genomic analyses of pig and related species.